2011
DOI: 10.1186/1478-4505-9-16
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of household and village characteristics on financial catastrophe and impoverishment due to health care spending in Western and Central Rural China: A multilevel analysis

Abstract: ObjectiveThe study aimed to examine the effect of household and community characteristics on financial catastrophe and impoverishment due to health payment in Western and Central Rural China.MethodsA household survey was conducted in 2008 in Hebei and Shaanxi provinces and the Inner Mongolia Autonomous Region using a multi-stage sampling technique. Independent variables included village characteristics, household income, chronic illness status, health care use and health spending. A composite contextual variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
5
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 24 publications
7
42
5
2
Order By: Relevance
“…These households do not have enough money for payment, especially for health care; therefore, they are pushed to the under poverty line. In line with the study, Shi found that households whose head was unemployed were more likely to incur financial catastrophe and impoverishment due to health expenditure (21). In addition, other studies confirm the present study (3,4).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These households do not have enough money for payment, especially for health care; therefore, they are pushed to the under poverty line. In line with the study, Shi found that households whose head was unemployed were more likely to incur financial catastrophe and impoverishment due to health expenditure (21). In addition, other studies confirm the present study (3,4).…”
Section: Discussionsupporting
confidence: 91%
“…However, the most studies showed that lowest economic group face more than the upper groups (20). A study done in China showed that 36.2 of the house- holds in the lowest economic status were impoverished by health care expenditure (21). The findings of various studies performed in both developing and developed countries have also confirmed the effect of the households' economic status on their being faced with poverty and CHE (16,22,23).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Saat ini, di Cina, keikutsertaan penderita dalam skema asuransi belum mampu memberi perlindungan terhadap kebangkrutan ekonomi keluarga dalam pembiayaan pelayanan kesehatan penderita yang mengalami penyakit katastropik seperti talasemia ini. 2 Penelitian ini bertujuan untuk menganalisis ability to pay, willingness to pay, dan need assessment pembiayaan kesehatan penderita talasemia di Kabupaten Banyumas.…”
Section: Jurusan Kesehatan Masyarakat Fakultas Kedokteran Dan Ilmu Keunclassified
“…One of the main goals of the system is to address catastrophic medical payments [14]. Since the launch of the NRCMS, access to and utilization of medical care among rural residents has improved [8, 15].…”
Section: Introductionmentioning
confidence: 99%